2009
DOI: 10.1080/13685530903150812
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in men with and without the metabolic syndrome

Abstract: The objective of this study was to measure bone mineral density (BMD) in middle-aged men with and without the metabolic syndrome according to the International diabetes federation (IDF) definition from 2005. We studied 80 men (mean age: 51.9 +/- 9.0 y, mean body mass index (BMI): 32.0 +/- 1.7 kg/m2) with and 92 men without the metabolic syndrome (mean age: 52.6 +/- 15.1 y, mean BMI: 24.9 +/- 2.8 kg/m2). Height (cm), weight (kg), waist circumference (cm) and blood pressure were measured. Fasting plasma glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…The researchers also found that with increasing number in components of MS, the femoral neck BMD of the subjects increased [ 17 ]. The positive relationship between MS and BMD was also reported by Boyanov et al in Bulgarian men [ 16 ], Pasco et al in Australian men [ 24 ] and Yamaguchi et al in Japanese men with type-2 diabetes [ 25 ]. Muhlen et al reported an interesting finding in Rancho Bernardo Study, in which age-adjusted femoral neck BMD was significantly higher in men with MS compared to men without MS [ 26 ].…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The researchers also found that with increasing number in components of MS, the femoral neck BMD of the subjects increased [ 17 ]. The positive relationship between MS and BMD was also reported by Boyanov et al in Bulgarian men [ 16 ], Pasco et al in Australian men [ 24 ] and Yamaguchi et al in Japanese men with type-2 diabetes [ 25 ]. Muhlen et al reported an interesting finding in Rancho Bernardo Study, in which age-adjusted femoral neck BMD was significantly higher in men with MS compared to men without MS [ 26 ].…”
Section: Discussionsupporting
confidence: 72%
“…The presence of metabolic syndrome has been associated with variations in bone mass measured by dual-energy X-ray absorptiometry (DEXA) and calcaneal quantitative ultrasonometry (QUS) in men. However, the results obtained are heterogeneous, whereby positive [ 16 , 17 ], negative [ 18 ] and non-significant [ 19 , 20 ] associations have been reported. Due to the limited number of studies available, no conclusive statement can be drawn on whether MS exerts beneficial or adverse effects on bone health in men.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the positive effect of metabolic syndrome and abdominal obesity on BMD disappeared after adjustment. However, data regarding metabolic syndrome and BMD are conflicting ( 39 , 40 ). Among all components of metabolic syndrome, waist circumference had the strongest correlation with lower BMD ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two reports which also choose IDF criteria for MS found different association between MS and BMD assessed by DXA. The study in Korean showed a negative association [17], whereas a Bulgaria study [18] confirmed the trend for higher BMD in men with MS.…”
Section: Discussionmentioning
confidence: 99%